Severe head & neck injury and its prevention in judo - Miyazaki, S. (Sports injuries and prevention, 2015)
Severe cases of concussion commonly occur in Judo practice. Therefore, it is important to know how to prevent this type of injury in Judo practice as well as how to respond to a concussed individual.